2007
DOI: 10.2202/1556-3758.1093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dry Ice and Superchilling on Quality and Shelf Life of Arctic Charr (Salvelinus alpinus) Fillets

Abstract: The influence of different cooling techniques (dry ice/ice packs) and storage temperature (-2°C/3°C) to prolong the shelf life of Arctic charr (Salvelinus alpinus) fillets were evaluated by sensory analysis, physical methods, chemical and microbial analysis. The effects of storage temperature were stronger than of different cooling agents. Superchilling (-2°C) of fillets packed with dry ice resulted in 6 days extension of shelf life compared to chilling (3°C). The use of dry ice parallel to superchilling pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 45 publications
2
22
0
1
Order By: Relevance
“…Contrary to us [34] reported that sensory score is the limit for acceptability of rainbow trout fillets to only 5 days at 3°C and 11 days at -3°C, but similarly to as connected the sensory scores with TAC, TVB-N, and K value. Contrary to us [35] were determined that super chilling (-2°C) of Arctic charr (Salvelinus alpinus) fillets packed [40]. Cathepsins B and B+L were not deactivated in portions of fillets of farmed Atlantic salmon (Salmo salar) super chilled at -1.4°C and -3.6°C [40].…”
Section: Ph Valuementioning
confidence: 58%
“…Contrary to us [34] reported that sensory score is the limit for acceptability of rainbow trout fillets to only 5 days at 3°C and 11 days at -3°C, but similarly to as connected the sensory scores with TAC, TVB-N, and K value. Contrary to us [35] were determined that super chilling (-2°C) of Arctic charr (Salvelinus alpinus) fillets packed [40]. Cathepsins B and B+L were not deactivated in portions of fillets of farmed Atlantic salmon (Salmo salar) super chilled at -1.4°C and -3.6°C [40].…”
Section: Ph Valuementioning
confidence: 58%
“…It was stated that the limit value of mesophilic aerobic bacteria in fresh fish was 6-7 log cfu/g and this value must be lower than 5 log cfu/g in a qualified product (Huss, 1988;Aguilera et al, 1992;Chytiri et al, 2004;Köse and Erdem, 2004;Bilgin et al, 2006;Cakli et al, 2006a;Bao et al, 2007;Duyar et al, 2012). Also it was stated that the limit value of psychrophile bacteria must be 5 log cfu/g (Erkan and Özden, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of sensorial scoring, they determined that raw product stayed within the quality limits during 12-15 days and the cooked product stayed within the quality limits during 15-17days. Bao et al (2007) determinated that the limit value of Salvelinus alpinus fillets under dry ice and super refrigerated conditions was 13 days in terms of sensorial. Rezaei et al (2008) researched the quality evaluations of rainbow trouts in ice and they determined that consumable value of trouts in terms of sensorial was 12 days.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these studies have focused on the chemical, microbiology and physical analyses of foods in superchilling (Bahuaud et al 2008;Beaufort et al 2009;Duun andRustad 2007, 2008;Erikson et al 2011;Gallart-Jornet et al 2007;Ando et al 2004;Bao et al 2007). Very few studies show the relationship between ice crystals development and quality of food during superchilled storage.…”
Section: Introductionmentioning
confidence: 99%